2014
DOI: 10.1016/j.rssm.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The transmission of longevity across generations: The case of the settler Cape Colony

Abstract: Evidence on long-term multigenerational dynamics is often inadequate as large datasets with multiple generations remain very uncommon. We posit that genealogical records can offer a valuable alternative. Rather than exploring the intergenerational transmission of socioeconomic status, we rely on birth and death dates of eighteenth and nineteenth century settlers in South Africa's Cape Colony to estimate the intergenerational transmission of longevity. We find that there is a positive and significant associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…"Inheritance of longevity" has been discussed at length in the literature. Its precise nature is somewhat elusive (Christensen, Johnson, & Vaupel, 2006;Pal and Tyler, 2016;Piraino, Muller, Cilliers, & Fourie, 2014;Vaupel et al, 1998). Gudmundsson et al (2000), studying the entire Icelandic population, concluded that longevity was inherited within families, in their view probably because of shared genes.…”
Section: Introductionmentioning
confidence: 99%
“…"Inheritance of longevity" has been discussed at length in the literature. Its precise nature is somewhat elusive (Christensen, Johnson, & Vaupel, 2006;Pal and Tyler, 2016;Piraino, Muller, Cilliers, & Fourie, 2014;Vaupel et al, 1998). Gudmundsson et al (2000), studying the entire Icelandic population, concluded that longevity was inherited within families, in their view probably because of shared genes.…”
Section: Introductionmentioning
confidence: 99%
“…“Inheritance of longevity” has been discussed at length in the literature. Its precise nature is somewhat elusive ( Vaupel et al, 1998 , Christensen et al, 2006 , Pal and Tyler, 2016 , Piraino et al, 2014 ). Gudmundsson et al (2000) , studying the entire Icelandic population, concluded that longevity was inherited within families, in their view probably because of shared genes.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, stronger maternal lifespan and longevity effects on offspring survival were found (Bocquet-Appel & Jakobi, 1990;Kemkes-Grottenthaler, 2004;Kerber et al, 2001;Piraino et al, 2014;Salaris, Tedesco & Poulain, 2013;Westendorp & Kirkwood, 2001). These studies offered possible explanations of longevity being transmitted by mitochondrial DNA (mtDNA) since offspring obtain mtDNA only through mothers .…”
Section: Discussionmentioning
confidence: 88%